FEEDING PATTERN EFFECT ON ORAL HEALTH PARAMETERS AND SALIVARY IL-6 LEVEL AMONG PRESCHOOL CHILDREN - Alwan Majbil , Dhaffar; Mohammed Jabber , Wathba; A. Yaseen , Huda; Nahidh , Mohammed; Alsadoon , Zeid (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Interleukin-6 plays a role in both regenerative and anti-inflammatory processes as well as inflammatory reactions. Various cytokines can be produced as a result of caries, which can then trigger oral immune reactions. Different inflammatory states, such as gingivitis, periodontitis, and oral lichen planus, were discovered to have high cytokine levels.This study aimed to evaluate the effect of feeding patterns on oral health parameters (dental caries, gingival health status) and age by measuring the level of salivary IL-6. Material and methods: The study sample included 61 children aged 4-6 years old divided into two groups (breastfeeding group and formula feeding group). The examination of the oral cavity was done on the basic method of oral health surveys of the World Health Organization by using dmfs, plaque, and gingival index according to recording protocols to measure the severity of dental caries and gingivitis. Saliva samples were collected and subjected to an enzyme-linked immunosorbent assay (ELISA) test to measure the level of IL-6.Results: Data of the present study showed a highly significant difference in salivary IL-6 levels between the breastfeeding group and formula-feeding group, and the median level of IL-6 was 5.5 in the breastfeeding group while in the formula-feeding group, it was 32.2. The results were statistically significant in the breastfeeding group between IL-6 and caries rate dmfs (p0.048), IL-6 and gingival index (p0.035), and dmfs with age (p0.049), while for formula feeding group these results were statistically non-significant.  Conclusion: In preschool-aged caries rate (dmfs) is strongly correlated to the salivary IL-6 level.  IL-6 level has a potent relation to the gingival index with a positive direction so it can be used as an early indicator for the presence of gingivitis and carious lesion. Breastfeeding has a direct effect to reduce the level of salivary IL-6 so it will affect the correlation between IL-6 levels and oral health parameters.